Character’s duality in the dictator’s novel - MALEK , Youcef Islam (Journal of Human Sciences, 2022)
This research proposes a study on duality in three novels which fall under the subgenre of the dictator’s novel: The Last Night Of The Rais by Yasmina Khadra, The autumn of the Patriarch by Gabriel Garcia Marquez and Waiting For The Vote Of The Wild Beasts of Ahmadou Kourouma. The study approaches the dual character through the character of El Gaddafi, the character of the president, and the character of Koyaga. The authors shape the dictatorial being through the character who represents it offering us a psychological model that is akin to the universal image of the despotic figure. An image where the character goes through a multitude of representations and where duality takes a preponderant place reflecting both his being and the image of his political regime. This duality will be studied in the light of the comparative method to show its different manifestations in the dictator’s novel.